2010
DOI: 10.1007/s10608-010-9295-1
|View full text |Cite
|
Sign up to set email alerts
|

Shared Variance Among Self-Report and Behavioral Measures of Distress Intolerance

Abstract: Distress intolerance may be an important individual difference variable in understanding maladaptive coping responses across diagnostic categories. However, the measurement of distress intolerance remains inconsistent across studies and little evidence for convergent validity among existing measures is available. This study evaluated the overlap among self-report and behavioral measures of distress intolerance in four samples, including an unselected sample, a sample of patients with drug dependence, and two s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
140
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 195 publications
(164 citation statements)
references
References 31 publications
21
140
3
Order By: Relevance
“…It is important to also note that, consistent with prior studies (Marshall-Berenz et al, 2010;McHugh et al, 2011), we observed self-report distress tolerance (DTS) not to be significantly associated with the employed behavioral measure of distress tolerance (i.e., MTPT-C). Here, the contexts in which the two forms of distress tolerance were assessed differ.…”
Section: C Dsupporting
confidence: 87%
See 3 more Smart Citations
“…It is important to also note that, consistent with prior studies (Marshall-Berenz et al, 2010;McHugh et al, 2011), we observed self-report distress tolerance (DTS) not to be significantly associated with the employed behavioral measure of distress tolerance (i.e., MTPT-C). Here, the contexts in which the two forms of distress tolerance were assessed differ.…”
Section: C Dsupporting
confidence: 87%
“…Moreover, the perceived inability to handle distress is defined as a cognitive factor, broadly, whereas task persistence in the face of distress is defined behaviorally (McHugh & Otto, 2012b). The absence of significant associations between perceived and objective distress tolerance may be in part due to the different types of distress (e.g., anxiety, frustration) and measurement contexts (i.e., in vivo vs. self-reported perceptions; McHugh & Otto, 2012b;McHugh et al, 2011). In addition, the measurement of perceived distress tolerance relies on self-report, which presents a challenge because of the difficulty participants have in accurately reflecting upon and discriminating their sensitivity to distress from their tolerance of distress (McHugh & Otto, 2012b;Sloan & Kring, 2007).…”
Section: C Dmentioning
confidence: 99%
See 2 more Smart Citations
“…Future research could decrease this risk by utilizing multi-method approaches (e.g., behavioral distress tolerance tasks). Indeed, self-report and behavioral indices of distress tolerance are often not highly related Marshall-Berenz et al 2010;McHugh et al 2011). Fifth, the study criterion variables were limited to anxiety/depression variables.…”
Section: Discussionmentioning
confidence: 99%